Experimental investigation of the pd and dd reactions at ultralow collision energies with using plasma accelerators invited paper - Bystritsky V. M.; Gerasimov V. V.; Il`guzin D. A.; Krylov A. R.; Parzhitskii S. S.; Anan¢in P. S.; Dudkin G. N. Gennadiy Nikolaevich; Kaminskii V. L.; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Petrov A. V.; Ratakhin N. A.; et al. (2009, 2009)
В фонде НТБ ТПУ отсутствует